Predictors of Depression and Anxiety among Medical Students - Thapa, Bipin; Sapkota, Suman; Khanal, Anil; Aryal, Binod Kumar; Hu, Yifei (Journal of Nepal Health Research Council, 2023)
Background: Medical undergraduates are more prone to emotional distress in comparison to the general population and non-medical undergraduates. This study aimed to identify the prevalence and factors associated with depression and anxiety symptoms among undergraduate medical students. Methods: A cross-sectional study was conducted among 204 medical students in a medical institute in Kathmandu. Depression, Anxiety and Stress Scale-42 was used to identify the prevalence of depression and anxiety symptoms. The data were analyzed using multivariable logistic regression models.Results: The prevalence of depression and anxiety symptoms was 30.9% and 38.7% respectively. Depression symptoms were more likely to be prevalent among fourth and fifth-year students, with an adjusted odds ratio (aOR 1.96, 95% CI: 1.03-3.75) compared to second and third-year students, and those who failed in the last academic examination (aOR 2.55, 95% CI: 1.28-5.09). Anxiety symptoms were more prevalent among male students (aOR 2.11, 95% CI: 1.04-4.27), those who were from the relatively less advantaged ethnic group (aOR 2.08, 95% CI: 1.04-4.16) and those who stayed outside the dormitory (aOR 2.90, 95% CI: 1.46-5.78). Conclusions: The prevalence of depression and anxiety symptoms among medical students was high. Psychological support is needed to ensure the mental well-being of medical students. Keywords: Anxiety; DASS-42; depression; medical students.